BIMBINGAN DAN KONSELING ISLAM DALAM PERSPEKTIF AL-QUR’AN DAN HADITS - Jannatun Aini; Hasep Saputra; Emmi Kholilah Harahap (JURNAL ILMIAH NUSANTARA, 2024)
The purpose of this article is to explain the principles of counseling guidance found in the Koran. which favorably leads to a mentor's efforts to help someone overcome their problems in the best way. This situation was first implemented directly by Rasulullah SAW because of the spiritual value that Allah SWT provides guidance for those who seek guidance. His friends, such as Umar and Usman, then followed this step. Currently, counseling guidance is provided as an Islamic counseling service through several services such as al-tabayyun, al-hikmah, al-mau'idhah, and al-mujjadi. In this research, descriptive qualitative methods were used to conduct library research. It also uses a hermeneutic approach to analyze the content. Arabic words for counseling.